2008
DOI: 10.1542/peds.2008-0812
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability and Effect of State on Blood Pressure Measurements in Infants 1 to 3 Years of Age

Abstract: Systolic blood pressure can be accurately measured in the first 3 years after birth, but state modifies systolic blood pressure and must be determined at the time of measurement. Infants born at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
(21 reference statements)
2
13
0
7
Order By: Relevance
“…Infant state was recorded as calm versus noncalm at the time of each measurement. In a previous study [13], we validated the reproducibility and accuracy of this method and demonstrated the elevating effects of a noncalm state on SBP measurements. Inter-and intra-rater reliability for this method is excellent in infants aged 1-3 years [13].…”
Section: Methodsmentioning
confidence: 66%
See 3 more Smart Citations
“…Infant state was recorded as calm versus noncalm at the time of each measurement. In a previous study [13], we validated the reproducibility and accuracy of this method and demonstrated the elevating effects of a noncalm state on SBP measurements. Inter-and intra-rater reliability for this method is excellent in infants aged 1-3 years [13].…”
Section: Methodsmentioning
confidence: 66%
“…In a previous study [13], we validated the reproducibility and accuracy of this method and demonstrated the elevating effects of a noncalm state on SBP measurements. Inter-and intra-rater reliability for this method is excellent in infants aged 1-3 years [13]. Only SBP was measured since the pulse is detectable to 0 mmHg with Doppler amplification, and the association between SBP and cardiovascular disease is more robust than diastolic or mean BP [16].…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…The most consistent change is an increase in BP by as much as 20 mmHg when an infant is feeding, although even sucking on a pacifier/soother can increase the pressure by up to 10 mmHg. The reliability of repeat BP measurements on infants also decreases when infants are in a non-calm state [20]. As in older children, use of the proper cuff size is important and has been determined in neonates to be a cuff width to arm circumference ratio in the range of 0.45-0.55 [14,21].…”
Section: Blood Pressure Measurement In Infancymentioning
confidence: 99%